Current opportunities and challenges of immersive virtual reality for psychological research and application - Wrzus, Cornelia; Frenkel, Marie Ottilie; Schöne, Benjamin (Acta psychologica, 2024)
Immersive virtual reality (iVR), that is, digital stereoscopic 360° scenarios usually presented in head-mounted displays, has gained much popularity in medical, educational, and consumer contexts in the last years. Recently, psychological research started to utilize the theoretical and methodological advantages of iVR. Furthermore, understanding cognitive, emotional, and behavioral processes in iVR similar to real-life is a genuinely psychological, currently understudied topic. This article briefly reviews the current application of iVR in psychological research and related disciplines. The review presents empirical evidence for opportunities and strengths (e.g., realism, experimental control, effectiveness of therapeutic and educational interventions) as well as challenges and weaknesses (e.g., differences in experiencing presence, interacting with VR content including avatars, i.e., graphical representation of a person). The main part discusses areas requiring additional basic research, such as cognitive processes, socio-emotional processes during social interactions in iVR, and possible societal implications (e.g., fraud, VR-addiction). For both research and application, iVR offers a contemporary extension of the psychological toolkit, offering new avenues to investigate and enhance core phenomena of psychology such as cognition, affect, motivation, and behavior. Still, it is crucial to exercise caution in its application as excessive and careless use of iVR can pose risks to individuals' mental and physical well-being.